Upaya peningkatan kesehatan diri dan lingkungan pada masyarakat pinggiran Sungai Cenrana - Mithen Lululangi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program is aimed attarget communities, namely community groups living on theoutskirts of the Cenrana River, precisely in Baleng Village,Watampanua Village, Pammana Distric, Wajo Regency,which in daily life uses river water for its needs. The purposeof the Community Partnership Program carried out is toincrease the knowledge, attitudes and behavior of communitygroups on the importance of consuming clean water forhealth. In its efforts to obtain clean water that is suitable forconsumption and fulfill the health requirements, additionalknowledge is needed of water purification technology that canbe applied to the household. The method used is the lecturemethod, discussion and question and answer on socializationactivities, and the method of demonstration in trainingactivities. The results achieved are partner communities to beaware and skilled about the importance of consuming cleanwater and how to clear water so that it becomes feasible toconsume